2008
DOI: 10.1124/dmd.108.021311
|View full text |Cite
|
Sign up to set email alerts
|

Covariation of Human Microsomal Protein Per Gram of Liver with Age: Absence of Influence of Operator and Sample Storage May Justify Interlaboratory Data Pooling

Abstract: The use of in vitro-in vivo extrapolation (IVIVE) of metabolic data in the prediction of population clearance has become an important tool in both discovery and preclinical phases of the drug development process (Rostami-Hodjegan and Tucker, 2007). Scaling of metabolic rate constants derived using microsomal protein (MSP) isolated from human livers or those from recombinantly expressed cytochrome P450 enzymes requires knowledge of the amount of microsomal protein per gram of liver (MPPGL) among other scaling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
111
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 15 publications
10
111
0
Order By: Relevance
“…3 and 4 and experimental intrinsic clearances (V max /K m ), assuming a liver size of 1500 g and a hepatic flow rate of 1.5 l/min for adults. Microsomal protein per gram of liver (MPPGL) was unknown, so the standard variable of 40 mg/g (Barter et al, 2008) was used for adults and in the allometric model. Because no values for 4MU blood unbound fraction exist, the f u for HEK293 cell lysate was 0.95.…”
Section: Methodsmentioning
confidence: 99%
“…3 and 4 and experimental intrinsic clearances (V max /K m ), assuming a liver size of 1500 g and a hepatic flow rate of 1.5 l/min for adults. Microsomal protein per gram of liver (MPPGL) was unknown, so the standard variable of 40 mg/g (Barter et al, 2008) was used for adults and in the allometric model. Because no values for 4MU blood unbound fraction exist, the f u for HEK293 cell lysate was 0.95.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the low number of subjects (total of 23) and methodological differences (cortex vs. mixed kidney or unspecified region), it is challenging to assess the impact of potential covariates (e.g. age and gender) on the kidney microsomal protein content, as previously done for liver microsomal protein (89). No data currently exist for human CPPGK, and research is ongoing to expand the available data for human MPPGK (90).…”
Section: Microsomal and Cytosolic Protein Content Of Kidneymentioning
confidence: 99%
“…The resulting RF (1 2 fractional loss of MSP) can be used to calculate a corrected MPPGL (eq. 2) (Barter et al, 2008).…”
Section: Protein Losses In Centrifugation: the Utility Of Recovery Famentioning
confidence: 99%
“…However, estimates of procedural losses of target proteins incurred throughout membrane fractionation have not been reported. Our group showed that the recovery factor (RF) for enzymes might be dependent on the procedure and the operator (Barter et al, 2008). However, on application of the relevant RF, estimation of the abundance in the tissue becomes less sensitive to operator differences, and variability between laboratories should be reduced.…”
Section: Introductionmentioning
confidence: 99%